The Usage of Abbreviation and Misspelling in DOTA 2’s Player Chat Logs: A Morphological Perspective - Marten, Timotius Delwin (Language Horizon: Journal of Language Studies, 2021)
The usage of Abbreviation, along with the common occurrence of Typographical Error and Misspelling are considered as normal in digital era right now. These aspects also commonly occurred in some virtual chat inside a video game, one of them being the Defenders of The Ancients 2 or also known as DOTA 2 by millennial kids these days. This study then created with a purpose to research about how much abbreviation affect communication between players in DOTA 2. The other purpose is to see if the occurrence of misspelling and typographical error affects something to the players. The method used in this research is by using theory from Crystal, (2003: 1) and Kallom (1917), It will used as a guide to detect and separate the word that may contain Abbreviation and Misspelling from the sentence. The word later on will compiled into each own categories and will be used as the data in this research. The data will be showed in form of table to ease the reader to understand it. The findings from this research show that abbreviations have a specific purpose in DOTA 2. The next finding also shows that Typographical Error and Misspelling is considered normal because of several factors.